when body becomes writing (gender, culture and sexuality) - Beltran, Myra C. (Review of Women's Studies; Vol 17 No 1-2 (2007): Review of Women's Studies Volume XVII, Numbers 1-2 (January-December 2007), 2023)
Dance, using Derrida's concept of the "trace," occurs in a signifying field or continuum. Thus the article states that not all of dance actually materializes as visible, [as it] questions to what extent dance is visible and what that visual data can tell us. This [essay presents a] writing about dance and [the author's] specific experience of it, in a manner that does not fix the frame in one visual field, and one specific, identifiable genre of dance. Rather, [she tries] to locate [her] practice by referencing the various forces that impinge on [her] body, [her] dancing body, that is the source, verifier, medium of all the dances that [she] creates. [She] wishes to recreate the tactile experience of [her] dancing body and hope[s] that [she] displace[s] any of the [reader's] inherited notions of dance, gathered most likely, from visual perceptions of it.